2005
DOI: 10.1590/s0100-84042005000400010
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal variations of non-structural carbohydrates in vegetative tissues of Melinis minutiflora, Echinolaena inflexa and Lolium multiflorum (Poaceae)

Abstract: -(Diurnal variations of non-structural carbohydrates in vegetative tissues of Melinis minutiflora, Echinolaena inflexa, and Lolium multiflorum -Poaceae). Echinolaena inflexa (Poir.) Chase is a native C3 grass species with high biomass production and abundance in the cerrado comparable to Melinis minutiflora Beauv., a C4 forage grass of African origin, widespread in the cerrado, displacing some native herbaceous species. These species accumulate mainly starch, differently of Lolium multiflorum Lam. ssp. italicu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 27 publications
2
12
0
3
Order By: Relevance
“…Most of the water soluble carbohydrates (WSC) in all parts of plants of Lolium multiflorum was composed of fructose polymers (figure 2), confirming previous information that fructans are the main reserve carbohydrates in this temperate forage grass (Souza et al, 2005), even when cultivated in a glasshouse under a subtropical environment.…”
Section: Resultssupporting
confidence: 85%
“…Most of the water soluble carbohydrates (WSC) in all parts of plants of Lolium multiflorum was composed of fructose polymers (figure 2), confirming previous information that fructans are the main reserve carbohydrates in this temperate forage grass (Souza et al, 2005), even when cultivated in a glasshouse under a subtropical environment.…”
Section: Resultssupporting
confidence: 85%
“…Comparative studies performed by Souza et al . () showed that the diurnal pattern of NSC in the perennial invasive grass Melinis minutiflora (C4) and in the Cerrado native grass E. inflexa (C3) was attributed to differences in starch metabolism, the main carbon reserve of these grasses, as also previously reported by Chatterton et al . () for other tropical grass species.…”
Section: Discussionsupporting
confidence: 75%
“…The diurnal pattern of NSC in both species (Souza et al, 2005) was at-variable and the accumulation of WSC, starch, glucose, fructose and sucrose as independent variables. The adjustment procedure started from the saturated model (with all the variables present); variables which had lower influence to explain phytomass variation (greatest value of p) were successively removed.…”
Section: Introductionmentioning
confidence: 98%